Das Schwingungsspektrum des synthetischen Carnotits - Baran, Enrique José (1976)
The infrared and laser-Raman spectra of synthetic carnotite, K₂[(UO₂)₂V₂O₈], are reported and discussed. Force constants for the terminal V-O bonds as well as for the UO₂²⁺ ions are evaluated. From the spectroscopic data, a U-O bond length of 1.81 A is estimated for the uranyl ion in this compound.